Is high‐risk neuroblastoma induction chemotherapy possible without G‐CSF? A pilot study of safety and treatment delays in the absence of primary prophylactic hematopoietic growth factors. Issue 10 (30th July 2020) - Whittle, Sarah B.; Smith, Valeria; Silverstein, Allison; Parmeter, Margaret; Minard, Charles G.; Bernhardt, M. Brooke; Zage, Peter E.; Venkatramani, Rajkumar; Nuchtern, Jed G.; Heczey, Andras; Russell, Heidi V.; Shohet, Jason M.; et al.
Abstract: Background/Objectives: Standard supportive care during induction therapy for high‐risk neuroblastoma (HR‐NBL) includes primary prophylactic granulocyte colony‐stimulating factor (G‐CSF) aimed at limiting duration of neutropenia, reducing infection risk, and minimizing treatment delays. Preclinical models suggest that G‐CSF promotes maintenance of neuroblastoma cancer stem cells and may reduce the efficacy of chemotherapy. This study's objective was to determine the safety and feasibility of administering induction chemotherapy without routine use of prophylactic G‐CSF. Design/Methods: Children with newly diagnosed HR‐NBL received six‐cycle induction chemotherapy regimen without prophylactic G‐CSF in four cycles. G‐CSF was administered for stem cell mobilization after cycle 3 and granulocyte‐monocyte colony‐stimulating factor after cycle 5 prior to surgical resection of primary disease. The primary outcome measure was the incidence of grade 3 or higher infection. We hypothesized that the per patient infection rate would be comparable to our institutional baseline rate of 58% in patients with HR‐NBL receiving induction chemotherapy with prophylactic growth factor support. The trial used an A'Hern single‐stage design. Results: Twelve patients with HR‐NBL received 58 cycles of chemotherapy on study. Three patients completed the entire six‐cycle regimen with no infections. Nine patients experienced grade 3 infections (bacteremia four, urinary tract infection two, skin/soft tissue infection three). No patients experienced grade 4 infections or required intensive care treatment for infection. Conclusion: A greater than expected number of serious bacterial infections were observed during administration of induction chemotherapy for HR‐NBL without primary prophylactic G‐CSF. These results support continued prophylactic administration growth factor during induction chemotherapy.